Comparison between upper thoracic spine mobilization and the Ergon technique in the treatment of mechanical neck pain - Said Zaghloul, Hebatalla M.; Osama Ghally, Shahesta A.; Talaat Abdelkhalek, Mona M.; Mohamed, Marwa T.; El-Din Mahmoud, Lama Saad; Osama Ghaly, Lamis A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Upper thoracic spine mobilization and the Ergon technique are used to treat mechanical neck pain in order to speed recovery, promote tissue healing and improve range of motion. There have been a few studies discussing the Ergon IASTM and upper thoracic spine mobilization in patients with neck pain, but none compared the aforementioned techniques in the treatment of mechanical neck pain. This clinical trial was conducted on a sample of thirty participants (16 females and 14 males) with mechanical neck pain who were randomly divided into two groups: Upper Thoracic Spine Mobilization (n=15) and Ergon Technique (n=15). Twelve sessions were delivered to all participants over a four-week period, three days per week. Before and after treatment, pain severity was measured by Numeric Pain Rating Scale (NPRS), cervical spine’s active range of motion was measured by using a Cervical Range of Motion (CROM) device, and cervical spine’s disability index was measured by Neck Disability Index (NDI). The statistical analysis was carried out using the Statistical Package for Social Sciences (SPSS) version 25. Both groups showed improvement in neck pain, reduced functional disability and increased cervical range of motion after treatment. The upper thoracic spine mobilization group had significantly better results in terms of cervical left lateral flexion and left rotation ranges of motion, while the Ergon Technique group had significantly better results in terms of improvement of neck pain and reduction in functional disability. In conclusion, the upper thoracic spine mobilization was effective at increasing the range of motion of the cervical region, while the Ergon technique was effective at relieving pain and dysfunction in the cervical spine in patients with mechanical neck pain.